Polymer Donors for High‐Performance Non‐Fullerene Organic Solar Cells. Issue 14 (17th January 2019) - Fu, Huiting; Wang, Zhaohui; Sun, Yanming
Abstract: Over the past few years, non‐fullerene organic solar cells have been a focus of research and their power conversion efficiencies have been improved dramatically from about 6 % to over 14 %. In addition to innovations in non‐fullerene acceptors, the ongoing development of polymer donors has contributed significantly to the rapid progress of non‐fullerene organic solar cell performance. This Minireview highlights the polymer donors that enable high‐performance non‐fullerene organic solar cells. We show the impressive photovoltaic devices results achieved by some of important classes of conjugated polymer systems in non‐fullerene organic solar cells. We discuss the molecular design strategies as far as developing matching polymer donors for non‐fullerene acceptors. We conclude with a brief summary and outlook for advances in donor polymers required for commercialization. Abstract : Polymer power : Polymer donors have shown remarkable photovoltaic performance in non‐fullerene organic solar cells (OSCs). The molecular design strategies are analyzed in terms of developing suitable polymer donors for non‐fullerene acceptors to further improve the power conversion efficiency (PCE) of non‐fullerene organic solar cells.